Antibacterial activity of a bacteriocin-like inhibitory substance produced by bacillus sp. From halophilic environment - VISHAL R. DHUNDALE; VIJAYSHREE M. HEMKE (International Journal of Pharma and Bio Sciences, 2017)
The objective of this study was to investigate a bacteriocin like inhibitory substance (BLIS) produced by a Bacillus sp. isolated from the halophilic Lonar crater. In present study total fourteen Bacillus sp isolated, out of them twelve Bacillus species showed that the antimicrobial activity against the E. coli and S. typhi except the CW1 and CW3. The Bacillus sp. CW2 was found 24 mm zone of inhibition that considered as prominent BLIS producer against E. coli while the Bacillus DS3 was found 25 mm zone of inhibition that considered as prominent BLIS producer against S. typhi. The Bacillus Sp. GW3 and Bacillus Sp. HS4 were found moderate activity with 22 mm zone of inhibition against P. aeruginosa and 28 mm zone of inhibition against P. vulgaris respectively. Out of fourteen, nine bacillus sp were found antibacterial activity against B. subtilis. The Bacillus Sp EW2 and Bacillus Sp. DS7 was found moderate activity with 21 mm zone of inhibition against B. subtilis and 22 mm against B. megaterium respectively. The isolated Bacillus sp. DS3 and DS2 were found antibacterial against all tested all gram positive bacteria. In conclusion, the studies suggested that halophilic environments could be sources of bacterial strains capable of synthesizing novel metabolites with antibacterial activity. These bacteria in general represent a new and rich source of BLIS that need to be explored